STRATEGI PENGELOLAAN DAN DISTRIBUSI DANA DI BANK WAKAF MIKRO ALMUNA BERKAH MANDIRI YOGYAKARTA TAHUN 2019 - Mutmainnah Mutmainnah; Mufti Afif (Journal of Islamic Economics and Philanthropy, 2020)
A strategy is needed by an institution to achieve the expected goals. With strategy management, a decision making process is created that leads to the development of an effective strategy. Micro Wakaf Bank is a new Islamic microfinance institution established by the President through the Financial Services Authority (OJK) as a community empowerment program around Islamic Boarding School. The name of the Micro Waqf Bank is only a branding to attract the interest of the community. But in accordance with the law, Micro Waqf Bank is a service cooperative. To run its programs, the Micro Waqf Bank needs a strategy, especially in the management and distribution of funds. By using qualitative methods presented in descriptive analytic supported by taking data sources with documentation, observation and interviews. Data analysis uses Miles and Huberman data analysis and SWOT analysis. This study aims to determine the management strategy and distribution of funds in the Micro Bank Almuna Berkah Mandiri Yogyakarta in 2019. The results of this study indicate that the Micro Wakaf Bank manages funds by providing microfinance without collateral to the community through the Community Groups Around the Indonesian Islamic Boarding School (Kumpi) and the joint responsibility system as a pattern in financing and business assistance through the establishment of Weekly Halaqah (Halmi). In its distribution, Almuna Berkah Mandiri Micro Endowment Bank uses qardh and jualah contracts. Then the calculation results of the SWOT analysis showed IFAS score of strength 2.63 and weakness 0.79 while the EFAS score of chance 2.63 and threat 1.13. And the strategy adopted is the SO (Strength & Opportunity) strategy, which is a strategy that seeks to exploit opportunities with the strength of the Micro Waqf Bank.